Cytological Analysis of Root Cultures of Artemisia Cina - Ermayanti, Tri Muji; Yanti, Oktavia; Hafiizh, Erwin Al (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2004)
Artemisia cina is a medicinal plant species producing bioactive compounds which are potential as antitumor, antifungal and antibacterial. The aim of this study was to analyze the stabililY of chromosome number in root cultures of A. cina. Transformed root culture was established by infection of leaves of A. cina with Agrobacterium rhizogenes strains 07-20001 . ATCC-15834. A4 and A. tumefaciens strain RlOOO . Roots isolated from glasshouse plants, plantlets grown in solid and liquid MS medium were utilized for investigation of chromosome examination of untransformed roots. Chromosome examination was conducted by squashing method and chromosome numbers were calculated under microscope. The .results showed that both untransformed and transforme root had instability in the chromosome number, but had the modal number of chromosome x=8 with the diploid number of 2n = 4x = 32. Roots isolated from glasshouse plants of A. Cina had 53.7% of cell with the diploid numbers of 2n = 32 and 46.3% of cells had chromosome numbers ranged from 2n = 12 to 2n = 64. Untransformed roots isolated from plantlets cultured in solid medw had only 36.1 % or cells with chromo orne number of 2n = 32, and unlran fomled ro t5 grown in liquid medium had 49.4% of cells with 2n = 32. The chromosome numbers of A. Cina transformed roots was affected by trains of Agrobacterium. Root transformed with the bacterium Strain 07 -20001 showed lhe highest in normal chromosome number of 2n = 32 (62.4%) followed by roots lransformed wiLll strains ATCC-15834 (61.9 %). R1000 (43.6%) and A4 (43.0%). The range of the chromosome number untransformed roots was from 2n= 17 to 2n=64 whilst that of transformed roots was from 2n= 1 l to 20=66